The Influence of the Frequency of Visits by Relatives, Social Interaction and Self Esteem on Depression in Elderly People in Homes for the Elderly in Nakhon Pathom Province - บรรยงคิด, สมฤดี; เลค, วิภา; เตียวกุล, สมชาย (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this study was to study the influence of the frequency of visits by relatives, social Interaction, and self-esteem on depression in elderly people in six homes for the elderly in Nakhon Pathom Province. Subjects included of 45 elderly simple randomized from the population. The study tools were: 1) the information record form for the elderly on frequencies of visits by relatives and participation in the activities provided by the home for the elderly. 2) Social interaction scale, 3) the Rosenberg self-esteem scale, 4) Thai Geriatric Depression Scale, and 5) guideline for conversation and interview with the elderly. According to the multiple regression analysis, it was found that only the self-esteem scale had the influence on the elderly’s depression significantly while the beta was -0.34 which can predict the elderly’s depression by 20%. The frequencies of visits by relatives and social interaction did not have the influence on the prediction for depression.